2022
DOI: 10.1186/s12967-022-03323-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary vessel density correlates with visual field mean sensitivity in highly myopic eyes

Abstract: Purpose To identify the global and regional distribution of peripapillary vessel density (pVD) and try to find out the relationships between pVD and the visual field mean sensitivity (VFMS) in healthy myopic eyes. Design Prospective cross-sectional study. Methods Two hundred and twenty-two participants (393 eyes) with myopia (myopic refractive error < − 0.5 diopters) from two clinical centers were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Despite a signi cant spatial correlation between decreased retinal vessel density and decreased visual eld sensitivity, [30] the fovea was still slightly inferior to the disc center in an eye with a rotated disc, which means the spatial relationship between the optic disc and the fovea remains. [19] Hence, the decrease in the superior DVD and the increase in the temporal DVD caused by the optic disc rotation may mainly be attributed to the redistribution of retinal vessels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite a signi cant spatial correlation between decreased retinal vessel density and decreased visual eld sensitivity, [30] the fovea was still slightly inferior to the disc center in an eye with a rotated disc, which means the spatial relationship between the optic disc and the fovea remains. [19] Hence, the decrease in the superior DVD and the increase in the temporal DVD caused by the optic disc rotation may mainly be attributed to the redistribution of retinal vessels.…”
Section: Discussionmentioning
confidence: 96%
“…There is a signi cant spatial correlation between decreased retinal vessel density and decreased visual eld sensitivity in myopic subjects. [30] Both elevated IOP and parapapillary hemodynamic disorder were associated with glaucoma. [31] In the current research, we found that the inferior rotation group had a higher IOP than the superior rotation group.…”
Section: Discussionmentioning
confidence: 99%
“…Its correlation with the spatially corresponding VF parameters is strong, and in some investigations, it was found stronger than that of the corresponding sector or global cpRNFLT 17–26 . This effect is particularly important in high myopia 12,27,28 . However, these are predominantly the findings of studies conducted on White Europeans and African American populations, while information on cpRNFLT-function and cpVD-function relationships of Japanese population with OAG eyes is limited 29–31 .…”
mentioning
confidence: 97%
“…However, both approaches have pros and cons; therefore, their combined use and evaluation are recommended 2–5 . Of the structural measures, circumpapillary retinal nerve fiber layer thickness (cpRNFLT), a highly reproducible parameter that suffers from floor effect in advanced glaucoma, 6–9 is considered less useful in eyes with both glaucoma and myopia due to myopia-related RNFL thinning and peripapillary atrophy 10–12 …”
mentioning
confidence: 99%
See 1 more Smart Citation